SISTEM PEMBERIAN DANA KARTU JAKARTA PINTAR (KJP) DENGAN MENGGUNAKAN METODE TOPSIS - YULI KOMALASARI (Paradigma, 2019)
The Jakarta Smart Card Program (KJP) has been carried out by various educational institutions at the elementary school level for almost seven years. There are 3 (three) criteria for determining whether or not students deserve the KJP assistance fund. Each criterion consists of several stages of sub criteria. The first criterion is to look at Household Member Information consisting of 6 (six) sub criteria, then the second criteria is to look at socio-economic conditions. This socio-economic condition consists of 5 (five) sub-criteria, and the third condition is to look at the condition of household assets consisting of 8 (eight) sub-criteria. The methodology / research approach used in evaluating the KJP program is to use the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The research was conducted to evaluate KJP funds whether it was on target, namely at the YAMPI Madrasah Ibtidaiyah (MI) school. Samples were taken from 5th grade students. The results of calculations using the Topsis method for the first, second and third grade students of MI YAMPI Al - Muttaqien were Elvara Salsabila, Kevin Erlin Fadhillah and Murti Diah Rahayu.